(untitled) (Dhaka University Journal of Science, 2024)
Plastic particles less than 5 mm in size, known as microplastics, can infiltrate the environment from a variety of sources. This study aimed to assess the presence of microplastics (MPs) in the atmosphere at fifteen major traffic intersections in the greater Dhaka city from July to August 2022.The deposition rate (DP) of MPs was calculated and the observed DPs value ranged from 1.11×106 MPs/m2/day to 5.78×106 MPs/m2/day with a portion of microplastics exhibiting fluorescence activity. Fourier Transform Infrared (FTIR) spectroscopy was used to analyze the functional groups present in microplastics. The identified polymer compositions of MPs were polyethylene (PE), Nylon-6 and natural polymers (cellulose and rubber). The current study highlights the data and knowledge gaps on the atmospheric transport of microplastics and their impact to the deterioration of overall urban air quality. Dhaka Univ. J. Sci. 72(2): 15-24, 2024 (July)